Analysis of protective immune responses to seasonal influenza vaccination in HIV-infected individuals. Issue 1 (2nd January 2021) - Xia, Ying; Mi, Fuli; Du, Guoqiang; Qin, Shenghui
ABSTRACT: Owing to their increased susceptibility to influenza infection, HIV+ individuals are recommended to receive annual influenza vaccination. However, influenza vaccination induced production of anti-influenza neutralization antibodies (Nab) is successful only in some viral-suppressed antiretroviral therapy (ART) treated HIV+ subjects. Additionally, the mechanism of antibody response induced by influenza vaccine in antiretroviral-treated HIV+ subjects is unclear. In this study, we conducted a cohort study which contains 40 HIV+ ART-treated individuals to whom one dose of seasonal influenza vaccine was administered. Blood samples were collected on day 0, 7, 14, and 28 post-vaccination, and serologic responses were characterized by ELISA and micro-neutralization to measure the total antibodies and Nab against influenza vaccines. Transcriptional profiling of peripheral blood mononuclear cells (PBMCs) and immunological assays was measured. Increased levels of proliferation of CD4+T cells and B cells with their corresponding subtypes were observed in HIV-infected subjects at day 7 (D7) following vaccination compared to pre-vaccination. Moreover, proliferation of CD4+T cells and B cells (D7) was correlated with influenza-specific H1N1 Nab at day 28 (D28). Our study could also demonstrate that apoptosis of CD4+T cells and B cells (D7) were inversely correlated with influenza-specific H1N1 Nab. Based on the Nab response after vaccination to each influenza subtypes (D28), HIV+ subjects were stratified as influenza vaccine responders and influenza vaccine non-responders ("responders" ≥ 4-fold increase from day 0; "non-responders" < 4-fold increase from day 0). A selected list of biological pathways (H1N1and H3N2: olfactory transduction, B: phagosome) enriched with transcripts were significantly altered in (ART) treated HIV+ subjects among Nab production responders. This study demonstrated a more detailed mechanism of immune regulation on influenza induced antibody response and revealed some knowledge regarding bioinformatics of vaccine responders and non-responder in influenza induced antibody production in ART-treated HIV patients.